Phenotypic characteristics of the p.Asn215Ser (p.N215S) GLA mutation in male and female patients with Fabry disease: A multicenter Fabry Registry study - Germain, Dominique P; Brand, Eva; Burlina, Alessandro; Cecchi, Franco; Garman, Scott C; Kempf, Judy; Laney, Dawn A; Linhart, Aleš; Maródi, László; Nicholls, Kathy; Ortiz, Alberto; Pieruzzi, Federico; et al. (Molecular genetics & genomic medicine, 2018)
BACKGROUND: The p.Asn215Ser or p.N215S GLA variant has been associated with late-onset cardiac variant of Fabry disease. METHODS: To expand on the scarce phenotype data, we analyzed natural history data from 125 p.N215S patients (66 females, 59 males) enrolled in the Fabry Registry (NCT00196742) and compared it with data from 401 patients (237 females, 164 males) harboring mutations associated with classic Fabry disease. We evaluated interventricular septum thickness (IVST), left ventricular posterior wall thickness (LVPWT), estimated glomerular filtration rate and severe clinical events. RESULTS: In p.N215S males, mildly abnormal mean IVST and LVPWT values were observed in patients aged 25-34 years, and values gradually increased with advancing age. Mean values were similar to those of classic males. In p.N215S females, these abnormalities occurred primarily in patients aged 55-64 years. Severe clinical events in p.N215S patients were mainly cardiac (males 31%, females 8%) while renal and cerebrovascular events were rare. Renal impairment occurred in 17% of p.N215S males (mostly in patients aged 65-74 years), and rarely in females (3%). CONCLUSION: p.N215S is a disease-causing mutation with severe clinical manifestations found primarily in the heart. Cardiac involvement may become as severe as in classic Fabry patients, especially in males.
Keywords: p.N215S; phenotype; GLA; Fabry disease; p.Asn215Ser; cardiac variant